Tribological optimization of titanium-based PVD multilayer hard coatings deposited on steels used for cold rolling applications. (March 2023) - Carabillò, A.; Sordetti, F.; Querini, M.; Magnan, M.; Azzolini, O.; Fedrizzi, L.; Lanzutti, A.
Abstract: The cold rolling process is used to produce very thin steel wires by compressive forces applied through a set of rolls. These rolls undergo to surface fast degradation due to high Hertzian stresses. In industrial applications, Physical Vapor Deposition (PVD) coatings are widespread deposits used to reduce the wear of mechanical components. The main aim of the work is to increase the wear resistance of the rolls by using the PVD coatings. In detail, this study is divided into two parts: the first parts deals with an optimization, in terms of process parameters and number of layers, of TiN/TiCN deposited by means of CAE (Cathodic Arc Evaporation) on both AISI D2 and AISI H13 steel. The deposits were characterized in terms of microstructure (SEM+EDXS analysis), chemical composition (Rf-GDOES measurements), mechanical properties (microhardness, scratch tests) and wear performances (pin on flat tests at loads closed to the service loads of cold rollers, by using an alumina counter material). The worn areas were then characterized to determine the wear rate and the wear mechanisms on each analyzed sample. The laboratory scale results showed a relation between the chemical composition of the coating and both the mechanical performances and the wear resistance. With these results, an optimum deposition process was defined and then used to coat the steel rolls that were employed in cold rolling mills. The service life of coated rolls was doubled, respect to the uncoated rollers. Graphical Abstract: ga1 Highlights: TiN/TiCN multilayer coatings are deposited on AISI D2 and AISI H13 steels for cold rolling applications. The thin films have been studied at different Substrate Bias Voltage (SBV) and microstructures. Tribological laboratory tests have identified the best performing multilayer and process parameters. Long-term durability of the coated rollers was achieved during a field test campaign.